2013
DOI: 10.1111/j.1365-2230.2012.04460.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of spectrophotometric intracutaneous analysis in the noninvasive diagnosis of nonmelanoma skin cancers

Abstract: Our findings show that dermatoscopic findings are more valuable than SIAscopic and clinical findings for the noninvasive diagnosis of NMSC. We consider that SIAscopy makes no substantial contribution towards the differential diagnosis of NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Using complex mathematical models, captured remitted light signals are processed to determine the haemoglobin and melanin content of the skin. Both the contact and non-contact SIAscope are novel methods for the diagnosis of melanoma and non-melanoma skin cancers [23][24][25]. Scanoskin TM , an adapted D-SLR camera, acts as a noncontact SIAscope customised for burn depth assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Using complex mathematical models, captured remitted light signals are processed to determine the haemoglobin and melanin content of the skin. Both the contact and non-contact SIAscope are novel methods for the diagnosis of melanoma and non-melanoma skin cancers [23][24][25]. Scanoskin TM , an adapted D-SLR camera, acts as a noncontact SIAscope customised for burn depth assessment.…”
Section: Introductionmentioning
confidence: 99%
“…A number of optical imaging and spectroscopic technologies have been developed for noninvasive detection of skin cancers . These include RCM, optical coherence tomography (OCT), diffuse reflectance spectroscopy including multi‐ and hyper‐spectral approaches, two‐photon microscopy, Raman spectroscopy, and multimodal spectroscopy . Of these, RCM imaging is currently the furthest along in clinical settings, with level I and level II evidence supporting its role in enabling dermatologists to discriminate benign from malignant lesions with high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated range of sensitivity of 78–96% and specificity 46–9%, depending on use of MelaFind alone or in combination with clinical examination and dermoscopy . Another multispectral approach, called spectro‐photometric intracutaneous analysis (SIAscopy or MoleMate), performs with sensitivity of 84–98% and specificity of 84–46% for melanocytic and non‐melanocytic lesions . Other developments include multi‐ and hyper‐spectroscopy, reporting range of sensitivities from 69% to 97% and specificities from 72% to 87% .…”
Section: Introductionmentioning
confidence: 99%
“…а -клиническое изображение; б -последовательно дерматоскопическое изображение, СИАсканы общего меланина, дермального меланина, распределения гемоглобина и коллагена. злокачественных новообразований кожи (НОК) [5][6][7][8]. Изначально предназначенная для ранней диагностики меланомы кожи СИАскопия вскоре доказала свою высокую чувствительность и специфичность для диагностики других НОК [9].…”
Section: Abstract: Spectrophotometric Intradermal Analysis Siascopyunclassified